Assessing Iraqi EFL College of Basic Education Students Educational and Vocational Needs Of English Language Classroom - Emad Jasem Mohamed, Sadoon Salih Muttar (Opción, 2019)
The study aims at assessing Iraqi EFL Basic Education College of Students' Educational and Vocational Needs of English Language classroom via a questionnaire to specify the academic needs of students on 2 areas namely Educational needs, and Vocational needs. As a result, the researchers have got 39 items. The obtained results are that the Educational area and the Vocational area. In conclusion, EFL college students become more aware of their needs and start to assess them in a more mature manner thinking of their future needs as independent people who try to satisfy their life needs out of their studying.